Climate change and inclusive growth in Africa - Suleiman O. Mamman; Kazi Sohag; Attahir Babaji Abubakar (Cogent Economics & Finance, 2023)
Africa's pursuit of inclusive and sustainable economic growth is impeded by many challenges, including climate change, whose effect is most apparent in the continent's tropical regions. To this end, this study investigates the impact of climate change on achieving pro-poor economic growth in Africa. Predicated on poverty-inequality-climate analysis, the Augmented Mean Group (AMG) estimator is used to analyse data from 1996 to 2020 covering 51 African countries. The results reveal that climate change significantly impedes inclusive growth. Furthermore, evidence of a long-lasting negative effect of climate change on inclusive growth, which could be attributed to a lack of coping mechanisms among the poor and vulnerable groups, is found. Finally, the findings show a marginal impact of institutional quality and government spending on inclusive growth in the face of climate change. The study recommends more climate mitigation efforts and enhanced adaptation mechanisms, especially for the poor, as they are most vulnerable to the adverse effects of climate change.
Keywords: I30; O55; Q54; 330; Africa; climate change; inclusive growth; income inequality; poverty; sustainability